Humanitarian Disciplines Influence on the Foreign Students Adaptation Process at the Initial Stage of Education in the Medical Universities of Ukraine - Antonova, Kateryna (Pedagogical Discourse, 2012)
In this article the influence of the humanities on the adaptation of international students in the medical university is considered. Based on analysis of the concept of "adaptation" in the broad sense the meaning of "adaptation of foreign students" is outlined. Maladjusted factors of the process of foreign students adaptation, as well as their dependence on the characteristic peculiarities of foreign students at the medical university are singled out. The influence and the contribution of some disciplines of humanitarian block on the adaptation of foreign students in the educational environment of medical university are studied. It is concluded that "the Ukrainian (Russian) language as a foreign language" carries a significant and substantial potential for the adaptation of foreign students in the educational environment of medical university. Direct dependence of the effectiveness of the training of foreign students from the level of adaptation is offered.